Isolation of Teeth in Children: A Review - Prajna Nibedita Behuria (Institute of Medico-legal Publications Pvt Ltd, 2020)
Isolation is done for proper control of moisture, good accessibility and visibility, to provide adequate spacefor instrumentation and operation. Most of the children are non-cooperative during treatment. So, isolation ismandatorily necessary for pediatric patients. Studies have shown that there are successful retention rates ofadhesive restoration when a rubber dam is used rather than any other isolation technique. The judicious useof rubber dam ensures greater patient comfort and delivery of high-quality dental care to pediatric patients.